5.5k views
1 vote
Balance the chemical equation:

Mg₃N₂ + H₂O → Mg(OH)₂ + NH₃
Fill in the blanks with coefficients for balance:
Mg₃N₂ + __H₂O → __Mg(OH)₂ + __NH₃

User Scorer
by
7.6k points

1 Answer

4 votes

Final answer:

To balance the chemical equation Mg₃N₂ + H₂O → Mg(OH)₂ + NH₃, you need to ensure that each element has the same number of atoms on both sides of the equation. Follow the step-by-step explanation provided to balance the equation.

Step-by-step explanation:

To balance the chemical equation Mg₃N₂ + H₂O → Mg(OH)₂ + NH₃, we need to ensure that each element has the same number of atoms on both sides of the equation.

Step 1: Start with the elements that appear only once on each side of the equation. In this case, we start with the nitrogen (N).

Mg₃N₂ + H₂O → Mg(OH)₂ + NH₃

Step 2: Balance the nitrogen (N) by adding a coefficient of 2 in front of NH₃.

Mg₃N₂ + H₂O → Mg(OH)₂ + 2NH₃

Step 3: Next, balance the hydrogen (H) atoms. Currently, there are 2 hydrogen atoms on the left side, and 6 hydrogen atoms on the right side of the equation. Add a coefficient of 3 in front of H₂O to balance the hydrogen.

Mg₃N₂ + 3H₂O → Mg(OH)₂ + 2NH₃

Step 4: Finally, balance the oxygen (O) atoms. Currently, there are 3 oxygen atoms on the left side, and 4 oxygen atoms on the right side of the equation. Add a coefficient of 3 in front of Mg(OH)₂ to balance the oxygen.

Mg₃N₂ + 3H₂O → 3Mg(OH)₂ + 2NH₃

User Sliceoftime
by
6.4k points